2016
DOI: 10.1097/ccm.0000000000001670
|View full text |Cite
|
Sign up to set email alerts
|

The Fragility Index in Multicenter Randomized Controlled Critical Care Trials*

Abstract: In critical care trials reporting statistically significant effects on mortality, the findings often depend on a small number of events. Critical care clinicians should be wary of basing decisions on trials with a low fragility index. We advocate the reporting of fragility index for future trials in critical care to aid interpretation and decision making by clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
125
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(146 citation statements)
references
References 16 publications
12
125
2
7
Order By: Relevance
“…Indeed, a recent study noted that the statistical conclusions of over half of the identified randomized clinical trials could be flipped either by using a more conservative statistical test or just changing the number of deaths to survivors by two, even in multi-centered trials in adult ICUs where mortality rates are approximately three to four times as high as pediatric units. 10 Critical care in general—especially pediatric critical care, due to the relatively low mortality rate—needs a more frequent outcome than mortality for robust and reliable studies.…”
Section: Why Does Assessing Morbidity Matter For Pediatric Critical Cmentioning
confidence: 99%
“…Indeed, a recent study noted that the statistical conclusions of over half of the identified randomized clinical trials could be flipped either by using a more conservative statistical test or just changing the number of deaths to survivors by two, even in multi-centered trials in adult ICUs where mortality rates are approximately three to four times as high as pediatric units. 10 Critical care in general—especially pediatric critical care, due to the relatively low mortality rate—needs a more frequent outcome than mortality for robust and reliable studies.…”
Section: Why Does Assessing Morbidity Matter For Pediatric Critical Cmentioning
confidence: 99%
“…In one study, researchers reported positive results in 10 (14%) of 72 multicenter RCTs with mortality as the primary endpoint published before August 2006 [20]; in a second, investigators reported that 7 (18%) of 38 trials published in 5 major medical journals between 1999 and 2009 showed positive results [5]; and in a third study, in evaluating ICU-based trials published between January 2007 and May 2013 in 16 high-impact general or critical care journals, researchers identified that 3 (9%) of 34 were positive [21]. Authors of a more recent systematic review identified that 44 (5%) of 862 multicenter critical care medicine trials reported significant differences in mortality [22]. These data confirm that ICU-based trials with mortality endpoints are frequently negative and indicate that the median predictions of prior probability offered by survey respondents in our study are broadly congruent with the observed frequency of positive trials in the critical care medicine literature.…”
Section: Discussionmentioning
confidence: 99%
“…The final result of ELAIN -an absolute difference of 15.4% in 90 day mortality in favour of early RRTexceeds the survival benefit that one might expect from early RRT initiation or perhaps from any experimental intervention evaluated in a cohort of critically ill patients with an increased risk of death. Importantly, the ELAIN trial has a low fragility index of three (if three more deaths occurred in the early RRT group or three less deaths occurred in the delayed RRT group the trial would have showed no between-group difference in mortality) 9 . The instability and the likely inflation of the effect estimate in the ELAIN trial were appropriately acknowledged by the researchers.…”
Section: Sean M Bagshaw and Ron Waldmentioning
confidence: 99%